The Madagascan genus Dolurgocleptes Schedl (Coleoptera: Curculionidae, Scolytinae): description of a new species and transfer to the tribe Polygraphini - Jordal, Bjarte H. (Zootaxa, 2009)
A new species of the Malagasy genus Dolurgocleptes Schedl, 1965 is described and illustrated. This is the second species known for the genus, which is restricted to the montane rainforests of north-eastern Madagascar. Dolurgocleptes is transferred from the tribe Dryocoetini to Polygraphini and placed near Polygraphus Erichson, based on examination of internal and external morphological characters and molecular data from Elongation Factor-1α and Cytochrome Oxidase I.